REV1 coordinates a multi-faceted tolerance response to DNA alkylation damage and prevents chromosome shattering in Drosophila melanogaster. - Khodaverdian, Varandt; Sano, Tokio; Maggs, Lara R.; Tomarchio, Gina; Dias, Ana; Tran, Mai; Clairmont,Connor; McVey, Mitch (Tufts University. Tisch Library., 2025)
When replication forks encounter damaged DNA, cells utilize damage tolerance mechanisms to allow replication to proceed. These include translesion synthesis at the fork, postreplication gap filling, and template switching via fork reversal or homologous recombination. The extent to which these different damage tolerance mechanisms are utilized depends on cell, tissue, and developmental context-specific cues, the last two of which are poorly understood. To address this gap, we have investigated damage tolerance responses in Drosophila melanogaster. We report that tolerance of DNA alkylation damage in rapidly dividing larval tissues depends heavily on translesion synthesis. Furthermore, we show that the REV1 protein plays a multi-faceted role in damage tolerance in Drosophila. Larvae lacking REV1 are hypersensitive to methyl methanesulfonate (MMS) and have highly elevated levels of γ-H2Av (Drosophila γ-H2AX) foci and chromosome aberrations in MMS-treated tissues. Loss of the REV1 C-terminal domain (CTD), which recruits multiple translesion polymerases to damage sites, sensitizes flies to MMS. In the absence of the REV1 CTD, DNA polymerases eta and zeta become critical for MMS tolerance. In addition, flies lacking REV3, the catalytic subunit of polymerase zeta, require the deoxycytidyl transferase activity of REV1 to tolerate MMS. Together, our results demonstrate that Drosophila prioritize the use of multiple translesion polymerases to tolerate alkylation damage and highlight the critical role of REV1 in the coordination of this response to prevent genome instability.; Funding for open access publishing provided by the Tufts Faculty Research Awards Committee (FRAC)